2014
DOI: 10.2298/abs1401137j
|View full text |Cite
|
Sign up to set email alerts
|

Copper tolerance of Trichoderma species

Abstract: Some Trichoderma strains can persist in ecosystems with high concentrations of heavy metals. The aim of this research was to examine the variability of Trichoderma strains isolated from different ecosystems, based on their morphological properties and restriction analysis of ITS fragments. The fungal growth was tested on potato dextrose agar, amended with Cu(II) concentrations ranging from 0.25 to 10 mmol/l, in order to identify copper-resistant strains. The results indicate that some isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
7
2
Order By: Relevance
“…This is in accordance with investigations showing that the copper cation concentration at 0.75 mmol dm −3 promotes the growth of Trichoderma species. 13 Experiments performed on T. viride spore survival in CS/ ALG/(Cu+TV) revealed that during storage at room temperature the number of spores was almost constant in the smaller microcapsule, whereas in larger microcapsules somewhat increased (Table 1). It seems that smaller microcapsules were fully loaded with T. viride spores and there was no space for their germination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with investigations showing that the copper cation concentration at 0.75 mmol dm −3 promotes the growth of Trichoderma species. 13 Experiments performed on T. viride spore survival in CS/ ALG/(Cu+TV) revealed that during storage at room temperature the number of spores was almost constant in the smaller microcapsule, whereas in larger microcapsules somewhat increased (Table 1). It seems that smaller microcapsules were fully loaded with T. viride spores and there was no space for their germination.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the importance of T. viride as a biocontrol agent, showing a high ability to accumulate and compatibility with macro-and micronutrients, 12,13 simultaneous encapsulation of copper cations and T. viride could give wider opportunities in both plant nutrition and protection. The aim of this work was to prepare chitosan/alginate microcapsules simultaneously loaded with copper cations and T. viride (CS/(ALG/(Cu +TV)) for plant protection and nutrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they represent an alternative to conventional fertilizers and contribute to the conservation of soil biodiversity (Dominguez-Nuñez et al 2015). Soil microorganisms are getting more and more popular as bioremediation agents as well (Kavamura et al 2008Jovičić Petrović et al 2014;Atanasković et al 2015).…”
Section: Natures Solution : Beneficial Soil Microorganisms (Bm)mentioning
confidence: 99%
“…There efficiency could be further enhanced by inoculation of selected rhizospheric microbes in the plant rhizosphere [18,19]. Petrovic et al [20] isolated a Cu tolerance Trichoderma species capable of scavenging toxic Cu from the soil. Preliminary success inspired several researches to search novel yet potential microbial inoculants which have multifaceted mode of action including scavenging of heavy metals toxicity from the contaminated soil and water.…”
Section: Introductionmentioning
confidence: 99%